Cross-conjugated poly(selenylene vinylene)s. Issue 8 (23rd January 2019) - Zhang, Zhen; Qin, Yang
Abstract : Poly(selenylene vinylene) (PSV) is a close analog to the extensively studied poly(thienylene vinylene) (PTV) polymers, and possesses unique properties originating from the larger, more polarizable Se atoms. Abstract : Poly(selenylene vinylene) (PSV) is a close analog to the extensively studied poly(thienylene vinylene) (PTV) polymers, and possesses unique properties originating from the larger, more polarizable Se atoms. Currently, little is known about the structure–property relationships of PSV derivatives, caused by the lack of efficient synthetic methods that are capable of producing systematically varied polymer structures beyond the prototypical alkylated version. We report herein a facile synthetic methodology, combining acyclic diene metathesis (ADMET) and post-polymerization modification (PPM) techniques, for the preparation of a series of novel PSV polymers bearing different aromatic units cross-conjugated with the main-chain. Such structural modification allows fine-tuning of PSV electronic properties through main-chain/side-chain interactions and leads to fundamental understanding on the structure–property relationships of this class of unique materials. Our methodology is highly versatile in installing tailor-designed cross-conjugated side-chains to PSVs, as well as to other poly(arylene vinylene)s containing different heteroarenes.